Exploring understandability of leaflet information on diabetic foot care by interviewing diabetic patients in Kathmandu, Nepal . - Nilsson,Maria Olofsdotter (2012)
ABSTRACT: Introduction: Diabetic patients in Nepal typically receive general information on how to control the disease while preventive measures are still lacking. Instructions are often verbal and can easily be forgotten or misunderstood, which emphasizes the need for diabetic foot care information that patients can bring home and make use of, regardless of literacy level. Aim: to produce an information leaflet in Nepali regarding prevention of diabetic foot problems and to explore the understandability of the produced leaflet by interviewing diabetic patients in Kathmandu, Nepal. Method: a leaflet was produced based on best available evidence. The understandability of the leaflet was explored via 27 structured interviews with Nepalese diabetic patients. Data was analyzed via manifest content analysis. Findings: The interviews revealed that pictures showing actions to take, pictures in a bigger format and pictures with movement were easier to remember than do´s and don'ts and that symbols were difficult to understand especially for low literate and illiterate participants. Conclusion: The leaflet proved to be useful for diabetic patients in Nepal but its content needs to be explained, especially to low literate and illiterate patients, in order to ensure full understanding. Keywords: Nepal; Diabetes; Leaflet information; Understandability; Prevention